Nutritional and Anti-Nutritional Compositions of Kernel Almond Flour from Kent Variety Mango (Mangifera Indica L.) Grown in Northern Côte d’Ivoire - N’Guessan, Kouamé Rodrigue; Kablan, Ahmont Landry Claude; Toure, Abdoulaye; Zoro, Armel Fabrice; Kamagaté, Tidiane; Boni, Ahoussi Pascal; Guehi, Monnou Sophie; Coulibaly, Sara Atchoumtcho; Coulibaly, Adama (European Journal of Applied Sciences, 2023)
Mango is an important tropical fruit around the world which is subject of large-scale production and extensive marketing. Unfortunately, much of its production is discarded as waste, usually consisting of its peel and kernel. This leads to high losses in mango sector and also ecological problems. This study aims to characterize nutritional and anti-nutritional properties of almond flour from Kent mango kernel. Also, after sampling Kent kernels from dried mango factories of Korhogo (Northern Côte d’Ivoire), they were washed and sun dried at 32- 35°C for 10 hours a day during 8 days. The drying mango kernels were peeled and almonds inside were removed, cut into small pieces and sun-dried to constant mass. The dry almond were crushed to obtain flour. Some nutritional and anti-nutritional properties of flour were determined. For nutritional compositions, analysis show that almond flour contains 7.6±0.35% moisture, 4.25±0.04% protein, 16.14±0.21% lipids, 1.95±0.15% ash and 70.06±0.56% carbohydrates. In addition, this almond flour contains amino acids which are mostly including lysine and leucine with respectively content of 64.19% and 13.89%. Also, flour contains minerals between 1.70 and 0.2 % which most important are potassium, magnesium, calcium and phosphorus. The almonds flour is composed of vitamin C and vitamins B1, B2 and B9. Concerning anti-nutritional factors, analysis of almond flour show that it contains tannins and phytates with respectively content of 119.27±1.47 mg/100g and 65.82±0.28 mg/100g. These above results show that almond flour of Kent mango kernel can be used for food purposes after elimination of anti-nutritional factors.